A Conceptual Framework for Technology-Enhanced Learning Design: Bridging Pedagogy and Digital Innovation - Dita Septasari; Ikna Awaliyani; Nur Aminudin; Septika Ariyanti; Shima Asadi (CV. Media Inti Teknologi, 2026)
Background: Learning designs must be grounded in pedagogical principles and make appropriate use of technical advancements in light of the digital transformation of education. Nonetheless, there is still a disconnect in many educational environments between the use of technology and pedagogical requirements.Aims: The research objective is to develop a conceptual framework for Technology-Enhanced Learning Design that bridges pedagogical principles with digital innovation. The research scope included a literature analysis, a review of best practices, and initial validation through education and technology experts.Methods: This research employed a qualitative approach with conceptual analysis and expert validation methods. Data were collected through a systematic literature review (2020–2025) and interviews with education and technology experts. Analysis was conducted using a thematic approach to identify the key dimensions of the technology-based learning design framework.Results: Pedagogical (learner-centered design, active engagement, personalization), technological (interoperability, scalability, AI integration), and implementation (continuous evaluation, institutional context, user readiness) are the three primary dimensions of the conceptual framework that emerged from the research. Compared to earlier studies, this framework has demonstrated the ability to more thoroughly integrate digital innovation with pedagogical concepts.Conclusion: The significance of combining technology and pedagogy in learning design is emphasized by this study. Researchers, educators, and legislators can use the conceptual framework that is produced as a guide for creating digital learning that is more sustainable and successful.